Major threats for amphibian and reptiles species in the Transylvanian rivers' basins recommended monitoring methods - Mara Gyöngyvér (Tiscia monograph series, 2002)
The author tries to identify the major threats for amphibian and reptile species in the Transylvanian rivers' basins. The herpetological investigations were performed during summertime in the hydrographic basins of Cri?ul Negru, Some? and Olt rivers, in the period 1997-1999. Two monitoring methods were used, occasional findings and information from local people. The most important factor in the dcclinc of herpetofauna from Transylvanian river's basins seems to be the loss of natural habitats. But the author considers that it is the time for quantitative field research, for a better study of herpetofauna conservation status. Finally, a few monitoring methods are proposed.